Demographic patterns in technical vocabulary acquisition and retention strategies among ESL engineering students in India - V. Sabarethinam; D, Praveen Sam; Lakshmi A., Vijaya; Rajmohan R., Rajmohan (Research Journal in Advanced Humanities, 2026)
Technical vocabulary, the domain-specific terms, is central to ESL engineering students' access to disciplinary knowledge. This study investigates the range and interaction of Technical Vocabulary Acquisition and Retention Strategies (TVARSs) employed by ESL engineering undergraduates in Tamil Nadu, India. Forty strategies divided into 11 categories were examined with attention to patterns of use and learner rationales. Using a mixed-methods design, data were collected from 331 undergraduate engineering students from rural, semi-urban, and urban backgrounds through a structured questionnaire and semi-structured interviews. Descriptive, correlational, and network-based modelling analyses were done. Findings reveal that technical vocabulary acquisition operates as a networked system of interrelated strategies rather than isolated practices. Major strategies provide structural support for vocabulary acquisition, while low-frequency strategies help as connectors that enhance adaptability, transferability, and learning resilience across demographic contexts. Network analysis further demonstrates that effective vocabulary development depends more on strategic coordination than on the frequency of individual strategies. The study identifies demographic variation in strategy access linked to learning environments and technological resources, and argues for demographic-responsive instruction that strengthens core strategies, promotes integrative connector strategies, and supports equitable access to reflective and technology-assisted learning practices.